2014
DOI: 10.1074/jbc.m113.537696
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 9 (GDF9) Forms an Incoherent Feed-forward Loop Modulating Follicle-stimulating Hormone β-Subunit (FSHβ) Gene Expression

Abstract: Background:The mechanisms underlying differential regulation of gonadotropin subunit genes are not fully elucidated. Results: Gonadotrope growth differentiation factor 9 (GDF9) expression, which is suppressed by GnRH, stimulates FSH␤ expression. Conclusion: Autocrine secretion of GDF9 contributes to FSH biosynthesis. Significance: Regulation of FSH by GDF9 may contribute to gonadotrope function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…To our knowledge, however, there is no evidence that GnRH signals directly to the Fshb promoter via either of these proteins (39,43). This said, both newer and older data suggest that GnRH may stimulate FSH indirectly via regulation of TGF␤ superfamily ligands and/or their antagonists (135)(136)(137)(138)(139). Future efforts, particularly in vivo, should be committed to determining the extent to which GnRH regulation of FSH depends on activins or other members of the TGF␤ superfamily.…”
Section: What Are the Relative Roles Of Activins (Or Activinlike Ligamentioning
confidence: 80%
“…To our knowledge, however, there is no evidence that GnRH signals directly to the Fshb promoter via either of these proteins (39,43). This said, both newer and older data suggest that GnRH may stimulate FSH indirectly via regulation of TGF␤ superfamily ligands and/or their antagonists (135)(136)(137)(138)(139). Future efforts, particularly in vivo, should be committed to determining the extent to which GnRH regulation of FSH depends on activins or other members of the TGF␤ superfamily.…”
Section: What Are the Relative Roles Of Activins (Or Activinlike Ligamentioning
confidence: 80%
“…The human FSHB gene (MIM 136530;11p13; genomic sequence 4.2 kb), coding for the FSH β-subunit, consists of one non-coding exon plus two translated exons that encode the 129-amino acid preprotein. The mechanisms controlling the transcription of the FSHB gene are critical regulatory steps in the production of the FSH hormone [5][6][7][8]. These mechanisms are complex, involving the actions of tissue-specific and widely expressed transcription factors [9].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that GnRH activation of G␣ s in L␤T2 cells promotes Lhb but suppresses Fshb gene expression via secretion of inhibin ␣ (1). Conversely, secreted GDF9 is an autocrine inducer of Fshb and is preferentially suppressed by high frequency GnRH pulses in L␤T2 cells (37).…”
mentioning
confidence: 98%